Inventory and Analysis of Diversity of Insect on Shallot Cultivation in Saruran Hamlet, Enrekang Regency - Kurnia, Nani; Lodang, Hamka (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Shallots (Allium ascalonicum L.) are a highly popular plant both as a culinary spice and herbal medicine. Due to their economic benefits, many farmers cultivate them. Saruran Hamlet, located in Anggareja District, Enrekang Regency, is one of the areas where shallots are intensively cultivated. Farmers face a significant problem with high pest infestation rates. To manage this, chemical pest control using insecticides is employed. However, insecticides are toxic and increasingly expensive. To reduce pesticide use, pest control using light traps was implemented through the